The elite weightlifter's strength and speed qualities - Yukhno Y.O; Sergienko K.N; Khmelnitska I.V (Kharkov National Pedagogical University, 2010)
The problems of estimation of power and speed possibilities of skilled weightlifter's are considered. In an experiment used complex REV 9000. The method of biomechanics control is developed. It allows in optimum terms to estimate the level of development of separate biolinks of body of sportsman. Speed power possibilities of right extensor higher on the average on 13%. Razgibatel' has large readiness to active reduction in the conditions of considerable tensions.